Highly efficient solar-pumped Nd:YAG laser - Liang, Dawei (2021)
This research project is funded by the Science and Technology Foundation of Portuguese Ministry of Science, (PTDC/FIS/103599/2008) Technology and Higher Education (FCT-MCTES).